ZAMONAVIY AYOLLAR USTKI KIYIMLARIDAN XUDOYORXON O‘RDASI XANDASAVIY VA GRIX NAQSHLARIDAN FOYDALANIB LIBOS TO‘PLAMINI YARATISH - Boymatova Kamola Abduraxmon qizi, Ibrohimova Durdona Muxsinjon qizi, Rahmonova Sarvinozxon Abrorjon qizi, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
In this article, the forms of women's modern coats, the analysis of the fabrics used, the physical-mechanical and operational characteristics of their materials were studied, and as a result of these analyzes, a new assortment of modern and complex shaped dresses was developed for women using the national pattern.